Palestine’s foreign policy under Hamas: principles and practices - Alsarhi, Abeer; Ahmad, Zaid (International Institute for Science, Technology & Education, 2016)
This paper examines Palestine’s foreign policy under Hamas’s Government (2006-2013). The aim is to explore the major principles underpinning the formulation of its foreign policy. Data were collected through face-to-face interview with five key persons in Hamas, secondary data were collected from books, journals, newspapers, magazines, and other relevant resources. The analysis was done through descriptive-analytical method. The findings revealed that Hamas foreign policies were formulated based on six agenda, namely: Islamic ethics, strategic vision, supporting of the resistance, protection of the national interests, non-interference, and independency of decision. Resistance has remained the only means of struggle against the occupation. These principles would be critically measured and contextually analyzed to see the implications towards the protection of Palestinians and the Hamas interests.